Measurements of semiconductor solar structures - Lim, Anne Hong Ting. (2012)
With the depletion of fossils fuel, there is an increasing emphasis on solar energy. However, low efficiency has been produced by the single-junction solar cell. Multi-junction solar cells are developed to produce more power with high efficiency. This report will look into the measurement analysis of how the efficiency of the current triple junction solar cell would improve by making use of 1eV subcell.Light biasing different subcell based on their bandgap will cause maximum rate of absorption